Is the Bisphenol A Biradical Formed in the Pyrolysis of Polycarbonate? - Arulmozhiraja, Sundaram; Coote, Michelle L; Kitahara, Yuki; Juhász, Márta; Fujii, Toshihiro (The Journal of Physical Chemistry A, 2011)
An unknown species has been detected in the analysis of the products in a pyrolysis of polycarbonate using Li+ ion-attachment mass spectrometry (IAMS). The mass spectra exhibited a Li+ adduct peak at m/z 233 that was tentatively assigned to bisphenol A (BPA) biradical. Experimentally, this assignment was supported by the observation that the production rate increased under an inert nitrogen atmosphere. To further confirm the assignment, the stability of the BPA biradical to intramolecular rearrangement reactions as well as unimolecular decomposition has been analyzed via density functional theory calculations [B3LYP/6-311+G(3df,2p)]. The results show that the bisphenol A biradical is an open-shell biradical singlet that is stable to unimolecular decomposition. Although some of the proposed intramolecular rearrangement products have lower energies than those of the BPA diradical, these pathways have large reaction barriers and the kinetic lifetime of the radical is expected to be of the order of hours under the conditions of the experiment. The calculations also reveal that the bisphenol A diradical has large Li+ affinities supporting the fact that these Li+ complexes could be detected in the Li+ ion attachment mass spectrometry. On the basis of these results the Li+ adduct peak at m/z 233 detected in the pyrolysis of polycarbonate is assigned to the bisphenol A biradical.